The effect of noisome preparation methods in encapsulating 5-fluorouracil and real time cell assay against HCT-116 colon cancer cell line. Issue 12 (December 2022) - Ugorji, Onyinyechi Lydia; Umeh, Ogochukwu Ngozi Chidimma; Agubata, Chukwuma Obumneme; Adah, Dickson; Obitte, Nicholas Chinedu; Chukwu, Amarauche
Abstract: The formulation of niosomes is influenced by a number of variables, and these variables may eventually affect the formulation's outcome. One of the elements that can influence the physico-chemical properties of niosomes is the method used in preparation of the formulation. In this study, we established if various methods of preparation have any impact on the prepared vesicles when loaded with 5-fluorouracil. Thereafter, a real-time cell assay (an in vitro cytotoxicity test) against HCT-116 colon cancer cell lines was done on an optimised batch. 5-fluorouracil loaded niosomes were prepared with either Tween 60 or Span 60 by four different methods - namely thin film hydration (TFH), reverse phase evaporation (RPE), evaporation/sonication (EVP/SON), and the ethanol injection method (EIM). In vitro evaluations were done on the formulations, and these included particle size analysis, entrapment efficiency, scanning electron microscopy (SEM), photomicrography, drug release, polydispersity index, and Fourier transform infrared spectroscopy (FTIR). The effects of the preparation method and type of non-ionic surfactants on encapsulation efficiency, particle size, and in vitro drug release of the niosomes at pH 7.4 were evaluated. An in vitro cytotoxicity test (real time cell assay (RTCA)) against HCT-116 cells was carried out using the optimised formulation. Results showed physically stable formulations. The TFH method produced the smallest particle sizes (187 nm and 482 nm), while the EVP/SON method produced the largest particle sizes (4476 nm and 9111 nm). The Tween-based niosomes prepared by TFH or RPE had higher drug entrapment. The FTIR studies of niosomal formulations showed broad peaks at wavenumbers above 3000 cm −1, indicating strong hydrogen bonds. The RTCA showed 5-fluorouracil-loaded niosomes caused more sustained cell death compared to the pure drug and blank niosomes. The methods of preparation affected the particle size, polydispersity index, entrapment efficiency, and the physical stability of the vesicles. The thin film hydration method was more robust in the entrapped 5-fluorouracil and showed lower particle sizes when compared to all the other methods. RTCA showed sustained cell death in real time. Abstract : 5 Fluorouracil; Niosomes; Cholesterol; Tween 60; Span 60; RTCA